SerpinE2 promotes M2 polarization in macrophage to accelerate colorectal cancer progression - Liu, Hui-Long; Gao, XiaoSheng; Yang, WeiFeng; Li, Wang-Lin (Frontiers in Oncology, 2025)
BackgroundCell-cell crosstalk in the tumor microenvironment (TME) is crucial for cancer development and strongly correlates with clinical outcomes. Interpatient variability in tumor microenvironment composition and function poses ongoing challenges for personalized therapy selection, remaining a significant clinical problem. Serpin family E member 2 (SERPINE2) released from the tumor microenvironment exhibits significant regulatory functions in cancer progression but the role of SERPINE2 in the tumor microenvironment remains unclear. In this study, we want to investigate the potential mechanism of SERPINE2 in tumor microenvironment of colon cancer.MethodsBioinformatics analysis was used for exploring the mRNA expression level of SERPINE family in Pan-cancer, the prognostic significance of SERPINE family overexpression in four cancer types, the clinical relevance of SERPINE2 and the potential function of SERPINE2 in colorectal cancer. We conducted qRT-PCR, Western blot and ELISA to investigate the expression of SERPINE2. Additionally, Tissue chips, Transwell assays, Cell counting kit-8 assay, and co-culture system were used to evaluate the relationship between SERPINE2 and polarization of tumor-associated macrophages.ResultsBased on public database screening, the SERPINE family genes were significantly upregulated in various cancers, and high expression of SERPINE family genes in colorectal cancer was closely associated with poor prognosis. Compared to other family members, SERPINE2 showed a high expression level and was closely related to clinical malignant progression of colon cancer patients. co-expression network analysis, KEGG and GO analysis revealed that SERPINE2 expression correlates with tumor immunoregulation, division and proliferation. Immune infiltration analysis indicated a significant positive correlation between SERPINE2 and M2 macrophage infiltration, and tissue chip confirmed the correlation between SERPINE2 expression in colon cancer tissues and macrophage infiltration. Cell co-culture experiments further demonstrated that SERPINE2 secreted by colon cancer cells can induce polarization of M2 macrophages. Next, the recombinant protein SERPINE2 was observed to stimulate macrophage polarization. We found macrophages induced by SERPINE2 in co-culture with cancer cells accelerated cancer cell proliferation and migration.ConclusionOur study demonstrates that tumor-secreted SERPINE2 mediates a positive feedback loop between tumor cells and M2 macrophages to accelerate cancer progression, suggesting SERPINE2 may be as a promising therapeutic target for colon cancer treatment.